The use of online peer feedback in the ESL writing of UiTM Pulau Pinang diploma students / Marni Jamil - Jamil, Marni (2015)
The use of online collaborative learning has been widely used by educators in teaching and learning practices. The study investigated the responses of UiTM Pulau Pinang diploma students towards the use of online peer feedback in ESL writing. The study aimed to investigate the students’ perspectives on using online collaborative writing in writing an essay, to examine the students’ perceptions towards the usefulness of the features of Google Docs in online collaborative writing, to determine to what extent the students engage actively in providing online peer feedback on their peers’ essays and to identify the students’ insights about their confidence in essay writing after using online peer feedback through online collaborative writing. Mixed-methods research design was employed for this study. A total of 65 students were selected as the sample of this study. Three techniques were used for data collection, which were questionnaires, semi-structured interviews and online activity logs. The quantitative data were analysed by using SPSS 22.0, the interview transcripts were sorted by codes and themes, and the online activity logs were analysed according to the rubrics for Criteria for Assessing Quality in Online Discussion Forums by Nandi, Chang and Balbo (2012). It was found that ESL writers had positive perceptions towards the use of online collaborative writing and they participated actively in online discussions. Generally, the findings of the study highlighted the vast potentials of Web 2.0 technology in education to foster collaboration among ESL students in ESL writing. The findings could give further insights to policymakers, researchers, fellow academicians and pre-service teachers on the prospects of blended learning in diverse fields of education in Malaysia.